Prognostic Impact of Tumor-Associated Macrophages on Long-Term Oncologic Outcomes in Colorectal Cancer - Hyeong Chan Shin (MDPI AG, 2021)
This study evaluated the correlation between tumor-associated macrophages (TAMs) and long-term oncologic outcomes in colorectal cancer (CRC). We evaluated TAMs based on the expression of CD68, CD11c, and CD163 as optimal markers via immunohistochemistry in 148 patients with CRC who underwent surgical resection between September 1999 and August 2004. A high proportion of CD68-positive macrophages were associated with the occurrence of distant metastasis. A low proportion of CD11c-positive macrophages were associated with unfavorable overall survival (OS) and disease-free survival. CD11c-positive macrophages were found to act as independent prognostic factors for OS. An analysis of our long-term data indicated that TAMs are significantly associated with OS and prognosis in CRC.